Description and Molecular Characterization of a New Dorylaimid Nematode, Mesodorylaimus pini n. sp. (Nematoda: Dorylaimidae) from Korea - Mwamula Abraham Okki; Lee Sang Myeong; Jung Young Hak; Kim Yi Seul; Lee Dong Woon (Journal of Nematology, 2024)
Mesodorylaimus pini n. sp., a new species isolated from the bark and cambium layer of a dead black pine tree is characterized herein using integrative taxonomy, considering both morphological and molecular phylogenetic analyses of the 18S- and 28S-rRNA genes. Mesodorylaimus pini n. sp. is characterized by having a medium-sized body 1.50–1.89 mm long; lip region angular and offset by a depression; a relatively long odontostyle (17.0–19.0 μm); vulval opening a transverse slit, positioned slightly posteriorly; pars refringens vaginae with two elongated drop-shaped to spindle-shaped sclerotizations; an intestine-prerectum junction with a long anteriorly directed conical or tongue-like projection; a relatively long female tail (115–187 μm); spicules 48.0–57.0 μm long; and regularly spaced 7–8 ventromedian supplements. It is closest to M. subtilis, especially in having similar body length and number of ventromedian supplements but can be differentiated from M. subtilis by the longer odontostyle, tongue-like projection, and longer spicules. The phylogenies based on the 18S- and 28S-rRNA sequences showed a well-supported sister relation of M. pini n. sp. with M. subtilis, M. japonicus, M. bastiani, M. pseudobastiani, Calcaridorylaimus castaneae, C. heynsi, and other member species of the group.